Blended Learning: Strategi Pembelajaran Alternatif di Era New Normal SD Tunas Harapan - A. Mahendra; Chintya Marselina Br Ketaren; Della Karmila Br Surbakti; Emia Fransiska Br Barus; Kartika Situmeang; Maulinanda Indrapraja (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
The program to help students learn is a community service carried out at SD Tunas Harapan Tanjung Anom, which is located at Jl. Griya Permata II housing, Durian Jangak, Pancur Batu District, Deli Serdang Regency, North Sumatra, for 1 month starting from August 16, 2021 until August 22, 2021. The activities carried out in this service are teaching and learning activities in schools and assisting students in doing school assignments which are carried out for 1 month. Teachers or students can combine face-to-face learning and online learning which is called blended learning. Blended learning can bemake it easier for students and teachers to share and receive materials online. In addition to students can using advanced technology when learning online, students can still learn face to face directly. The material comes from thematic books and guide books from schools. In the implementation of this service, there are several obstacles such as: inadequate facilities, lack of attention from students in studying at home, lack of awareness of students about their responsibilities in doing assignments, lack of communication and parental attention to their children.